Terpenoid Mixtures as Repellents Against the American Cockroach: Their Synergy and Low Toxicity Against Non-Target Species - Passara, Hataichanok; Moungthipmalai, Tanapoom; Laosinwattana, Chamroon; Sittichok, Sirawut; Murata, Kouhei; Soonwera, Mayura (My University, 2026)
The repellent activities (Periplaneta americana) of lone and binary mixtures of terpenoids—geranial, trans-anethole, and trans-cinnamaldehyde—against adult American cockroaches were evaluated in this study. The respective efficacies of these mixtures were compared with that of 12% (w/w) DEET. Safety bioassays for all formulations on non-target species, namely, earthworms (Eudrilus eugeniae) and guppy fish (Poecilia reticulata), were conducted to identify natural compounds with repellent efficacy equal to or surpassing that of DEET while ensuring ecological safety for non-target organisms such as fish and earthworms. All mixtures (RC50 of 0.3 to 1.6 µL/cm3) were more effective than all lone terpenoids (RC50 of 6.2 to 9.1 µL/cm3) and DEET (RC50 of 3.0 µL/cm3), demonstrating strong synergy, with an increased repellent value (IV) of 79 to 96%. The strongest repellency, 98.0% at 72 h and an RC50 of 0.3 µL/cm3, was achieved using geranial + trans-cinnamaldehyde (1:1). This mixture was 5.9 to 10 times more effective as a repellent than DEET. The toxicity of every lone terpenoid and terpenoid mixture to non-target species was low; hence, these mixtures can be considered safe, whereas DEET was highly toxic to non-target species (100% mortality). The terpenoid mixture geranial + trans-cinnamaldehyde showed strong repellency against P. americana.
Keywords: geranial + trans-cinnamaldehyde; non-target earthworm and guppies; Periplaneta americana; synergistic repellent effect; terpenoid binary mixture